Metaphors in Vytautas Kavolis’s Sociology - Noreika, Alvydas (Sociologija. Mintis ir veiksmas, 2017)
This article deals with the question of what place do metaphors hold in Vytautas Kavolis’s sociology. By following Lithuanian researcher Algimantas Valantiejus, who first inquired into the question, it is asked whether Kavolis’s sociology is poetical entirely, or do the poetical means of expression play a limited role in it. It is argued that the last case is involved. Poetical images do not overly control the sociologist’s expression of thoughts and his construction and use of means of cognition in any of his field of research. It is stated that the only way to overcome the non-poetical features of Kavolis’s language and to declare his sociology poetical in nature is to presuppose that all scientific concepts are but developed metaphors and that they never lose relationships with their metaphoric origins. An acceptance of such a presupposition opens the possibility to look for poetical images behind any abstract concepts. It is stated that Valantiejus uses this possibility in poetizing the overall sociology of Kavolis. According to him, all non-poetic features of its language, as well as poetic ones, have their origins in the metaphor of painting. It is argued that Valantiejus’s choice of the fundamental metaphor of Kavolis’s sociology hasshortcomings. The image of painting cannot explain the whole scope of Kavolis’s sociological research and the variety of its theoretical presuppositions adequately. It is stated that these shortcomings can beeasily eliminated by expanding Valantiejus’s conception of painting and by including three additional poetical images into the list of the fundamental metaphors of Kavolis’s sociology – mechanism, drama and organism.
Keywords: Vytautas Kavolis; Algimantas Valantiejus; metaphors; sociological poetics; post-positivist philosophy of social sciences